Example:
x = √3x+71
x+1 = √3x+7
(x+1)Â² = (√3x+7)Â²
xÂ²+2x+1 = 3x+7
Question: Why +2x
xÂ²6x = 0
Question: Why 6x?
x = 2 OR x = 3
Question: How can you see the answer will be 2 or 3?

Example:
x = √3x+71
x+1 = √3x+7
(x+1)Â² = (√3x+7)Â²
xÂ²+2x+1 = 3x+7
Question: Why +2x
xÂ²6x = 0
Question: Why 6x?
x = 2 OR x = 3
Question: How can you see the answer will be 2 or 3?
to expand the squared bracket like your example (x+1)^2 you square the x and then the number(1) then you multiply 1 by x by 2 (the power above the square) about your second question you move the l.h.s to the R.H.S with an opposite sign it will be x^2 +2x+13x7=0 this is to be put in the form of the quadratic equation then you the equation becomes x^26x1=0 this is to be able to find the roots of the quadrtic equation by the quadratic formula or by factorizing .I hope this helps .
Sara,
Now I understand why I couldn't figure it out. I'm taking math and had forgotten all about it, so I'm starting from scratch. It's been many years. Thanks for reply though.
« irrational numbers .......underoot 2  mathematics of the mind » 